Decolourization of industrial dyes using Ascomycetes and mucor species - S VIJAYANAND; MOHIT MISRA (International Journal of Pharma and Bio Sciences, 2017)
The present study was conducted to investigate the decolourization of commercial industrial dyes using different types of fungal strains isolated from soil sample. Four fungal species were isolated and identified as Rhizopus stolonifer, Aspergillus niger, Yeast sp. and Penicillium sp. Decolourisation of the dye was optimized at suitable temperature and pH (30 ÌŠ C and pH 5). The effect of culture conditions (pH and temperature ) on decolourisation of Red RR azo dye, green and safranine were evaluated after transfer of fungal substrate in liquid media. Dyes were removed in 10 days after complete decolourisation by four fungal strains. The decolourisation of dyes was measured in terms of reverse OD. R.stolonifer was identified as best decolouriser of Red RR dye. A.niger and Penicillium sp. were identified as best decolourisers of Safranine dye. Yeast sp. was identified as best decolouriser of Green dye.